The concept of Universal ethics as a new general moral reality and the basis for a people’s culture - Donev, Dejan (Filozofski fakultet, Novi Sad, 2014)
The new life of mankind is filled with a variety of new phenomena and new ethical values from which most authentic is the idea of creating Universal ethics. Universal ethics is composed of two things: the unique system of ethical values and norms, and it is shares different experiences as ethical heritage of mankind. The construction of Universal ethics actually means putting into mutual contact of ethical ideas, most valuable of all nations and their associated overall. As such it can be seen as a medium for meeting of different cultures. So Universal ethics becomes a new general moral reality of the people and the new history of mankind, which will enable a new rise of human civilization.
Univerzalna etika kao nova opšta moralnost i kao osnova ljudske kulture
Keywords: ethics, universal, human life, culture, new general morality